RECIPROCAL TEACHING BERBANTUAN MEDIA PHYSICS SIMULATION TENTANG GAYA UNTUK MEREDUKSI MISKONSEPSI SISWA SMK - Dhaniyah, Ufy; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to investigate the effectiveness of implementation Reciprocal Teaching Model by Physics Simulation Media on reduced misconception of students about Force in SMK Negeri 2 Pontianak. The method of this research is pre-experimental by one-group pre-test post-test design. As the sample of this research, there are 27 students in X Teknik Permesinan class which are chosen by random sampling in technic of intact group. The tool for collecting data is 10 questions the form of multiple choice with the reasoning open. The mean percentage of declining misconception of students about Force after remediation class is 63%. Based on McNemar test, the change student conceptions obtained then there is a significant change in the students conceptions after remediation class. The Hatie?s effect size value is 3,24 and the Cohen?s effect size value is 6,63 which are categorized as high., then Reciprocal Teaching Model effective in the assited Physics Simulation Media in reducing students misconceptions. Keywords: Force, Misconception, Physicsc simulation, Reciprocal teaching model